Measurement invariance of the patient health questionnaire-9 depression scale in a nationally representative population-based sample - Lee, Eun-Hyun; Kang, Eun Hee; Kang, Hyun-Jung; Lee, Hyun Young (Frontiers in Psychology, 2023)
The Patient Health Questionnaire-9 (PHQ-9) is widely used to measure the severity of depressive symptoms and to screen for depressive disorder, but its measurement invariance has received little research attention. The aim of this study was to assess the measurement invariance of the PHQ-9 across various sociodemographic and medical-condition groups. The structural validity and internal consistency of the PHQ-9 were also assessed as the prerequisite properties for measurement invariance. This study was conducted using data from the Korea National Health and Nutrition Examination Survey. The included participants comprised 5,347 people older than 19 years. Exploratory graph analysis (EGA) and confirmatory factor analysis (CFA) were performed to determine structural validity, and the omega coefficient (ω) was used to determine internal consistency. Measurement invariance (configural, metric, and scalar invariance) was evaluated using multigroup confirmatory factor analysis (MGCFA). The single structural model of the PHQ-9 that was validated by EGA was also satisfactory with fit indices of χ2 = 770.765 (p < 0.001), CFI = 0.944, SRMR = 0.040, and RMSEA = 0.076 (90% CI = 0.072–0.081). The ω of the PHQ-9 was 0.812, implying satisfactory internal consistency. The one-factor PHQ-9 had equivalent overall structure, factor loadings, and item intercepts across age groups, suggesting invariance across ages. Partial scalar invariance was demonstrated across sex and marital-status groups. Partial metric and scalar invariance were supported across education groups. Scalar invariance was supported among all of the medical-condition (hypertension, diabetes, cancer, arthritis, asthma, and heart disease) groups. Overall, the measurement invariance of the one-factor PHQ-9 was empirically supported across sociodemographic and medical-condition groups. The PHQ-9 can be reliably used to compare the severity of depressive symptoms across these groups in research and practice.